Lungmask och löpmagsnematod hos nötkreatur - Stennemark, Veronika (SLU/Dept. of Animal Nutrition and Management (until 231231), 2011)
Infection with intestinal parasites can in many cases be the reason for decreased performance or production. The gastro-intestinal nematode, Ostertagia ostertagi, and the lungworm, Dictyocaulus viviparus, are the most pathogenic nematodes of cattle and severe infection can lead to death. They have both a direct lifecycle and on the pasture the parasites spread as freeliving worms. The parasites are mainly a problem for the first season grazers. They have not developed immunity against the parasites and are therefor more sensitive to parasite infections. The level of exposure that the first season grazers are subjected to determine the immunity to parasite infections in the second season grazers. A major alternative to anthelmintic treatment for preventive use, particulary in organic production, is a well adapted grazing system. A good grazing system is also important to reduce the use of anthelmintic drugs and reduce the risk that the parasites develop resistance to the anthelmintic substance. The parasites can overwinter both on pasture and in the host. They overwinter as inhibited larvae or as infective third stage of larvae. It is the overwintered larvae who infects the animals at turn-out in the spring. Few studies have been performed on their ability to survive in silage, but the few studies done show that after three months there appeer to be no infective larvae left. Silage which has been stored for three months are free from parasites and can therefor be used as feed to the animals.